(untitled) (Nepalese Journal of Radiology, 2023)
Human epidermal growth factor receptor-2 (HER 2) positive breast cancers represent a highly aggressive breast cancer subtype and are associated witha worse prognosis. They tend to be more aggressive with lower survival rates but with a better prognosis than the triple-negative subtype.